A New Activated Sludge Model with Membrane Separation–Implications for Sewage and Textile Effluent - Orhon, Derin; Yucel, Ayse Begum; Insel, Guclu; Duba, Seyda; Olmez-Hanci, Tugba; Solmaz, Bulent; Sözen, Seval (MDPI AG, 2021)
A new model for the activated sludge process with membrane separation is presented, based on the effective filtration size. A new size threshold is imposed by the membrane module. The model structure requires a modified fractionation of the chemical oxygen demand and includes chemical oxygen demand fractions entrapped in the reactor or in the flocs as model components. This way, it offers an accurate mechanistic interpretation of microbial mechanisms taking place in membrane activated sludge systems. Denim processing wastewater was selected for model implementation, which emphasized the significance of entrapped fractions of soluble hydrolysable and soluble inert chemical oxygen demand responsible for better effluent quality, while underlining the shortcomings of existing activated sludge models prescribed for systems with conventional gravity settling. The model also introduced particle size distribution analysis as a new experimental instrument complementing respirometric assessments, for an accurate description of chemical oxygen demand fractions with different biodegradation characteristics in related model evaluations.
Keywords: MASM; Chemical technology; denim processing wastewater; new model for membrane activated sludge; TP1-1185; Article; Chemical engineering; captured COD fractions; TP155-156; particle size distribution; modified COD fractionation